Proyeksi Ekspor-Impor Non-Migas Indonesia ke Afrika Selatan - Kumara Jati; Aziza Rahmaniar Salam (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2018)
This study analyzes the projection of Indonesia’s non-oil and gas exports and imports to South Africa. Indonesia’s trade policy needs to take into account the seasonal and irregularity conditions of trade between Indonesia and South Africa. The The Structural Time-Series Model (STSM) shows that the projected volume and value of Indonesia’s non-oil and gas exports to South Africa from 2018 to 2027 tends to stabilize with an upward trend. The relevant authorities need to pay more attention to the seasonal trade patterns where there is usually a fluctuation of exports and imports at the beginning and end of the year from Indonesia to South Africa. In addition, relevan stakeholders also need to anticipate if there is turmoil in overseas markets, especially South Africa because it can affect the trade between the two countries and the Indonesia economy in general.